What zinc supplementation does and does not achieve in diarrhea prevention: a systematic review and meta-analysis - Mamtani Manju; Patel Archana B; Badhoniya Neetu; Kulkarni Hemant (BMC Infectious Diseases, 2011)
Abstract Background Prevention of diarrhea has presented indomitable challenges. A preventive strategy that has received significant interest is zinc supplementation. Existing literature including quantitative meta-analyses and systematic reviews tend to show that zinc supplementation is beneficial however evidence to the contrary is augmenting. We therefore conducted an updated and comprehensive meta-analytical synthesis of the existing literature on the effect of zinc supplementation in prevention of diarrhea. Methods EMBASE®, MEDLINE ® and CINAHL® databases were searched for published reviews and meta-analyses on the use of zinc supplementation for the prevention childhood diarrhea. Additional RCTs published following the meta-analyses were also sought. Effect of zinc supplementation on the following five outcomes was studied: incidence of diarrhea, prevalence of diarrhea, incidence of persistent diarrhea, incidence of dysentery and incidence of mortality. The published RCTs were combined using random-effects meta-analyses, subgroup meta-analyses, meta-regression, cumulative meta-analyses and restricted meta-analyses to quantify and characterize the role of zinc supplementation with the afore stated outcomes. Results We found that zinc supplementation has a modest beneficial association (9% reduction) with incidence of diarrhea, a stronger beneficial association (19% reduction) with prevalence of diarrhea and occurrence of multiple diarrheal episodes (28% reduction) but there was significant unexplained heterogeneity across the studies for these associations. Age, continent of study origin, zinc salt and risk of bias contributed significantly to between studies heterogeneity. Zinc supplementation did not show statistically significant benefit in reducing the incidence of persistent diarrhea, dysentery or mortality. In most instances, the 95% prediction intervals for summary relative risk estimates straddled unity. Conclusions Demonstrable benefit of preventive zinc supplementation was observed against two of the five diarrhea-related outcomes but the prediction intervals straddled unity. Thus the evidence for a preventive benefit of zinc against diarrhea is inconclusive. Continued efforts are needed to better understand the sources of heterogeneity. The outcomes of zinc supplementation may be improved by identifying subgroups that need zinc supplementation.